Penggabungan Kearifan Lokal dan Teknopreneurship dalam Wisata Kuliner Desa Nongkosawit Gunungpati Semarang - Hendrajaya Hendrajaya; Heni Krisnatalia (Lembaga Pengembangan Kinerja Dosen, 2024)
Within the confront of fast worldwide nourishment patterns and modernization, concerns are rising almost the potential misfortune of nearby culinary conventions that exemplify a nation's imaginativeness, culture, history, and character. To address this, STIEPARI Semarang propelled a community benefit extend in Nongkosawit, Gunungpati, pointed at protecting and advancing its one of a kind culinary legacy. The venture included recording conventional formulas and their social centrality, guaranteeing that this information is passed down and shared. The group collaborated with neighborhood cooks to coordinated present day culinary methods whereas keeping up genuineness. Workshops were held to educate the community how to showcase their conventional dishes, emphasizing storytelling as a way to associate with visitors. To maintain these endeavors, the venture presented computerized stages for nearby culinary businesses to reach broader gatherings of people through social media and e-commerce. This activity not as it were jam Nongkosawit s culinary bequest but moreover engages the neighborhood community by making modern financial openings tied to their wealthy social conventions. Through these endeavors, Nongkosawit Town represents the significance of defending and celebrating culinary conventions that characterize our social personality.